Serial Backward Locomotor Treadmill Training Improves Bidirectional Walking Performance in Chronic Stroke - Awosika, Oluwole O.; Chan, Dorothy; Rizik, Bridget A.; Sucharew, Heidi J.; Boyne, Pierce; Bhattacharya, Amit; Dunning, Kari; Kissela, Brett M. (Frontiers in Neurology, 2022)
ABSTRACT Background and Research Question-- Walking impairment remains a major limitation to functional independence after stroke. Yet, comprehensive and effective strategies to improve walking function after stroke are presently limited. Backward Locomotor Treadmill Training (BLTT) is a promising training approach for improving walking function; however, little is known about its mechanism of effect or the relationship between backward walking training and resulting overground forward walking performance. This study aims to determine the effects of serial BLTT on spatial aspects of backward and forward walking in chronic post-stroke individuals with residual walking impairment. Methods-- Thirty-nine adults (>6 months post-stroke) underwent six days of BLTT (3x/week) over two weeks. Outcome measures included PRE-POST changes in backward and forward walking speeds, paretic and non-paretic step lengths, and single-support center of pressure distances. To determine the association between BLTT and overground walking, correlation analyses comparing training-related changes in these variables were performed. Results—We report an overall improvement in BLTT and overground walking speeds, bilateral step lengths, and single-support center of pressure distances over six training sessions. Further, there were weak positive associations between PRE-POST changes in BLTT speed, BLTT paretic step length, and overground forward walking speed. Conclusion and Significance— Our findings suggest that individuals with chronic post-stroke walking impairment experience improvements in spatial walking measures during BLTT and overground. Therefore, BLTT may be a potential adjunctive training approach for post-stroke walking rehabilitation.